Polyamine biosynthesis during germination of yeast ascospores. - Brawley, J V (1979)
The role of the diamine putrescine during germination and outgrowth of ascospores of Saccharomyces cerevisiae was examined. Ornithine decarboxylase activity increased and declined rapidly during germination and outgrowth; peak activity was attained after the cells had proceeded through the G1 interval of the cell cycle, whereas minimal activity was present at the completion of the first cell division. alpha-Methylornithine inhibited both ornithine decarboxylase activity and the in vivo accumulation of putrescine. In the presence of alpha-methylornithireak dormancy and proceed through one cell division. Subsequent cellular growth, however, was retarded but not completely inhibited. The supplementation of Methylglyoxal bis(guanylhydrazone) to sporulation medium greatly inhibited this sexual process. These data suggest that the synthesis of putrescine is not required for the breaking of spore dormancy, but that polyamine biosynthesis may be essential for meiosis and sporulation.